Escutar (r) Dora - Giora, Maria Inês; Klain, Wilson (Percurso, 1993)
Resenha de "A Histeria - o caso Dora: Freud, Melanie Klein, Jacques Lacan" - Chaim Samuel Katz. Rio de Janeiro, Imago Editora, 1992. 218 p.